2022
DOI: 10.1007/s12231-022-09545-8
|View full text |Cite
|
Sign up to set email alerts
|

Nubian Agricultural Practices, Crops and Foods: Changes in Living Memory on Ernetta Island, Northern Sudan

Abstract: Agricultural practices in northern Sudan have been changing rapidly but remain little documented. In this paper we aim to investigate changes to crops grown in living memory and their uses through interviews with Nubian farmers on the island of Ernetta. By exploring cultivation and crop processing practices, together with associated material culture and foodstuffs, we also seek to explore how agricultural and food heritage are connected, and to better understand reasons for crop changes. Several cereals and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Recent agricultural practices in Nubia provide a rich body of data suitable for informing past land use in the northern Sudanese Nile Valley (Ryan et al, 2022). Meanwhile, palaeobotanical studies have revealed some of the crop types grown in these landscapes, including during the second millennium B.C.E.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent agricultural practices in Nubia provide a rich body of data suitable for informing past land use in the northern Sudanese Nile Valley (Ryan et al, 2022). Meanwhile, palaeobotanical studies have revealed some of the crop types grown in these landscapes, including during the second millennium B.C.E.…”
Section: Discussionmentioning
confidence: 99%
“…Similar wells have also been noted close to walls on the banks of a large palaeochannel in the 3rd Cataract (Tahir & Sadig, 2014, p. 48). Shadufs continued to be used in Sudanese Nubia until very recently (Ryan et al, 2022, p. 255).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the importance of minor crops within cultural and food heritage paradigms, and the major role of this heritage in their long-term conservation, are also significant. As explained by Ryan et al [ 17 ], some minor crops, which tend to be of high local importance, have their own stories and “timing of change, being additionally connected to transitions in the ways they are processed and transformed into foods and to shifting food preferences”.…”
Section: Introductionmentioning
confidence: 99%